From this moment - Camden, Elizabeth, 1965- (Bethany House, a division of Baker Publishing Group, 2016)
Stella West's artistic talent made her the toast of London, but when her beloved sister dies under mysterious circumstances, she abandons everything, heads for Boston, and tries to pierce the ring of secrecy surrounding her sister's death. When she meets Romulus White, a publisher with innumerable connections, she decides he could be a valuable ally. He decides to help her as a means to induce her to create art for his magazine. Neither one is prepared for the sparks that fly, and Romulus begins to wonder whether helping Stella solve the mystery of her sister's death is worth the risk to his publishing empire.